Art of Love in Work of Ibn Hazm “Ring of Dove” - T. M. Aminov; M. T. Yakupov (Научный диалог, 2022)
The article deals with the problem of love relationship between a man and a woman presented in the work of the medieval thinker Ibn Hazm ‘The Ring of the Dove’. The choice of the writer and his work is caused by several reasons which have determined the research problem. The authors note existing gaps in the study of love themes in Ibn Hazm’s works. Moreover, the love theme becomes especially relevant nowadays because of the vast variety of attitudes to gender relations existing in the world and differing from conventional wisdom accepted by world religions and traditional national cultures. The aim of the study is to analyze the representations of the art of love in the work ‘The Ring of the Dove’. The authors draw on the studies of Russian, Arab, Persian and Central Asian scholars who reflected upon certain aspects of Ibn Hazm’s thinking. The authors come to the conclusion about Ibn Hazm’s deep understanding of psychological and pedagogical peculiarities defining love relationship between a man and a woman, who observe origins, types, signs and results of love. The description of the feeling is illustrated by means of multiple examples from real life and the author’s personal experience. It is argued that Ibn Hazm’s thoughts are still relevant today.